Epithelioid Trophoblastic Tumor: A Case Report and Review of the Literature - Eirwen M. Scott; Ashlee L. Smith; Mohamed Mokhtar Desouki; Alexander B. Olawaiye (Case Reports in Obstetrics and Gynecology)
Epithelioid trophoblastic tumor (ETT) is a rare gestational trophoblastic tumor. Cases of ETT present as abnormal vaginal bleeding in women of reproductive age, with low human chorionic gonadotropin (hCG) levels. ETT can be a sequela of any gestational event and can present in both intrauterine and extrauterine sites. Metastasis and death have been reported. We present a case of a 44-year-old female incidentally diagnosed with ETT following laparoscopic-assisted vaginal hysterectomy. Postoperative evaluation for metastatic disease was negative. The patient has been closely followed and remains disease free 8 months postoperatively. ETT presents a diagnostic challenge due to its rarity and histologic resemblance to other pathologies. ETT is relatively chemoresistant and managed surgically. Misdiagnosis delays effective treatment and affects survival.